2018
DOI: 10.18483/ijsci.1533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drought on Seed Germination and Early Seedling of Tomato Genotypes using Polyethylene Glycol 6000

Abstract: Tomato is a sensitive crop to a variety of environmental stresses, especially drought. Therefore, the objective of the present work was to screen for drought tolerance at seed and seedling (vegetative) levels for better understanding of drought mechanisms and identification and selection of the most tolerant tomato genotypes. Twenty four (24) tomato genotypes were screened for drought tolerance using 0%, 4% and 14% polyethylene glycol 6000 (PEG 6000). The experiment was laid in complete randomized design with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Drought that occurs causes impacts and problems for the world of agriculture, especially on the rate of productivity related to meeting the water needs of a plant (Sujinah and Jamil, 2016) (Venkatesh et al, 2018). Tomato (Solanum lycopersicum) is one of the horticultural crops whose productivity is threatened during the dry season (Esan et al, 2018). Tomato has various benefits and is in great demand by most people (Zhou et al, 2020), especially residents in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Drought that occurs causes impacts and problems for the world of agriculture, especially on the rate of productivity related to meeting the water needs of a plant (Sujinah and Jamil, 2016) (Venkatesh et al, 2018). Tomato (Solanum lycopersicum) is one of the horticultural crops whose productivity is threatened during the dry season (Esan et al, 2018). Tomato has various benefits and is in great demand by most people (Zhou et al, 2020), especially residents in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…PEG 6000 is a natural polymer, which is nontoxic and nonionic. PEG 6000 induces osmotic stress in plants by reducing water potential as it is observed during the shortage of rainfall [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…PEG molecules are too large to be absorbed by plant roots, so the increased PEG concentration in the surrounding environment causes the water to not be absorbed by the stem cells and thus the plant is exposed to water stress (Mohammadkhani et al, 2008;Hamayun et al, 2010). The drought stress created by PEG can also be used for in vitro screening tests, so a large number of genetic resources can be accurately screened with less effort (Kulkarni and Deshpande, 2007;Basha et al, 2015;Esan et al, 2018;Özkaynak and Şimşek, 2018). It has been reported that PEG concentrations ranging from 4% to 12.5% are suitable for screening of tomato genotypes against drought tolerance during germination and seedling stage (Ghebremariam et al, 2013;Jokanovic and Zdravkovic, 2015).…”
Section: Introductionmentioning
confidence: 99%